Lipid raft-dependent adhesion of Giardia intestinalis trophozoites to a cultured human enterocyte-like Caco-2/TC7 cell monolayer leads to cytoskeleton-dependent functional injuries - Humen, Martin Andres (2011)
Gardia intestinalis, the aetiological agent of giardiasis, one of the most common intestinal diseases in both developing and developed countries, induces a loss of epithelial barrier function and functional injuries of the enterocyte by mechanisms that remain unknown. Three possible mechanisms have been proposed: (i) Giardia may directly alter the epithelial barrier after a close interaction between the trophozoite and polarized intestinal cells, (ii) intestinal functions may be altered by factors secreted by Giardia including an ‘enterotoxin’, proteinases and lectins, and (iii) based on mouse studies, a mechanism involving the intervention of activated T lymphocytes. We used fully differentiated cultured human intestinal Caco‐2/TC7 cells forming a monolayer and expressing several polarized functions of enterocytes of small intestine to investigate the mechanisms by which G. intestinalis induces structural and functional alterations in the host intestinal epithelium. We first report that adhesion of G. intestinalis at the brush border of enterocyte‐like cells involves the lipid raft membrane microdomains of the trophozoite. We report an adhesion‐dependent disorganization of the apical F‐actin cytoskeleton that, in turn, results in a dramatic loss of distribution of functional brush border‐associated proteins, including sucrase‐isomaltase (SI), dipeptidylpeptidase IV (DPP IV) and fructose transporter, GLUT5, and a decrease in sucrose enzyme activity in G. intestinalis ‐infected enterocyte‐like cells. We observed that the G. intestinalis trophozoite promotes an adhesion‐dependent decrease in transepithelial electrical resistance (TER) accompanied by a rearrangement of functional tight junction (TJ)‐associated occludin, and delocalization of claudin‐1. Finally, we found that whereas the occludin rearrangement induced by G. intestinalis was related to apical F‐actin disorganization, the delocalization of claudin‐1 was not.